ASR, Volume 23, n° 1, 2019 - Full Issue (African Sociological Review, 2019)
Contents Editorial ..........................................................1 General Issue L’organisation Internationale de la Francophone : Instrument de Development ou de Dependence Par Dali Clement Stephane .......................................................4 Research Papers La contribution des Universités dans la mise en œuvre des ODD au Sénégal : le cas de l’Université Alioune Diop de Bambey Mamadou Saliou Mbengue .........................................................19 The reform of public universities in Tanzania: Governmentality and the exercise of power Maduekwe, Catherine, Chinenye & Beverly Thaver ...................................45 Transition énergétique et mouvements sociaux à Abidjan : une analyse dialectique des perceptions de la population abidjanaise face à la politique étatique de distribution d’ampoules à basse consommation Kabran Aristide Djane ..............................................................61 Transition from shacks to formal human settlements – Social cohesion in Mt Moriah in the metropolitan area of Durban, South Africa. Sultan Khan ................................................................79 De la présence féminine dans la rue : Stratégies d’accession à l’espace public dans un quartier spontané, Ras El Ain – Oran (Algérie) Mehdi Souiah ................................................................96 A Researcher’s Visit to Italy: Human trafficking and the Nigerian-Sicilian Mafias Mike Omilusi ..............................................................110